Efficiency and equality in a simple model of efficient unemployment insurance - Atkeson, Andrew 1961-; Lucas, Robert E. 1937-2023 (1993)
This paper describes the efficient allocation of consumption and work effort in an economy in which workers face idiosyncratic employment risk and considerations of moral hazard prevent full insurance. We impose a lower bound on the expected discounted utility that can be assigned to any agent from any date onward, and show, with this feature added, that the efficient unemployment insurance scheme induces an invariant cross sectional distribution of individual entitlements to utility. The paper thus provides a simple prototype model suited to the study of the normative question: what is the tradeoff between equality and efficiency in resource allocation?
Keywords: Mathematisches Modell; Resource allocation -- Mathematical models; Unemployment insurance -- Mathematical models